Pengaruh Persepsi Manfaat, Persepsi Kemudahan, dan Risiko Terhadap Minat Pengguna QRIS Sebagai Alat Pembayaran di Kalangan Masyarakat Medan: Penelitian - Khoirunnisa Naibaho; Onan Marakali Siregar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of the perception of benefits, perceptions of convenience and risk on the interest in the use of QRIS as a means of payment among the people of Medan either partially or simultaneously. The form of research used in this study is quantitative research with an associative approach. Sampling using Multi-Stage Sampling technique and using 100 respondents as a sample. The research conducted showed that the variable perception of benefit (X1) and perception of convenience (X2) have a positive and significant effect on the interest in the use of QRIS. while the risk (X3) does not affect the interest in the use of QRIS. However, the variables of benefit perception (X1), convenience perception (X2), and risk (X3) simultaneously affect the interest in the use of QRIS. The coefficient of determination test showed that there is a fairly close relationship between the perception of benefits, convenience and risk to the interest of using QRIS with an R value of 0.827. Through the value of adjusted R square is also known that the variable perception of benefit, convenience and risk contribute 0.674 to the interest in the use of QRIS while the remaining 32.6% are influenced by other variables that are not discussed in this study.